MALIGNANT TUBERCULOSIS - Saeed, Waseem (Journal of Ayub Medical College Abbottabad, 2006)
on and extensive disease are the most alarming.5 The greatest tragedy is the extensive form of the disease with irreversible structural distortion, fibrosis, cavitation, bronchiactasis, formation of perilesional emphysema and total lung destruction. Extensive tuberculosis behaves like malignancy, as rapidly advancing illness with wasting, cachexia and bleeding (hemoptysis). It has the penchant to disseminate to adjacent structures like pleura, lymph nodes or distant organ systems like bones and brain. Akin to a malignant lesion, chemotherapy is suboptimal, surgical intervention is impossible due to extensive involvement, leading to end stage lung disease with cor pulmanale, respiratory failure and death. J Ayub Med Coll Abbottabad 2006;18(3) 2 Pulmonary tuberculosis was romanticized in the arts and mu sic of the 19th century. The deaths of Mimi in Puccini’s La Boheme and Satine in Moulin Rouge are portrayed as romantic tragic events. However, end stage tuberculosis is anything but glamorous and Mimi and satine exposed everyone around them to danger with each breath. The dying faced night sweats, chills and paroxysmal cough, spreading the disease to other organs of the body, resulting in the wasting away that led helpless bystanders to name the disease consumption. Around 460 BC, Hippocrates identified phthisis or consumption in late stage as an incurable disease of his age. Because of that he advised his followers and students against treating such patients to avoid damage to their reputation. Yet in the 21st century it still remains the most devastating dilemma, where patients mostly young beg for help while physicians powerlessly watch them die. It is with this milieu that at the time of diagnosis of Pulmonary TB, the quantification into minimal, moderately advanced with and without cavitation and far advanced is imperative. As treatment with standard drugs in disseminated TB, tuberculous-lymphadentis, and moderately advanced with cavitation will not produce a rapid cure, causing a slowly responding patient to inevitably acquire irreversible structural damage. It is in this perspective that early expansion of therapy in moderately advanced tuberculosis will be a paradigm shift in the strategy of treating such patients upfront with effective, and offensive regimen, with a resolve to cure them and thus save them from end stage ’˜malignant tuberculosis’. If this hypothesis is perceived correctly it will be an epoch making change in the final outcome of managing tuberculosis. It will truly reflect the aspirations of the man who first discovered mycobacterium tuberculosis and remained the intellectual forerunner of tuberculosis control. Such was his fervor for finding a cure that he finished his Nobel lecture by reasserting his optimism: The fight has been ignited fully and the enthusiasm for this goal is so broad that I am not afraid that it will seize again. If we continue to work in such a powerful way victory will be achieved.